Effects of soy isoflavenes (genistein) on chemotherapy and radiotherapy toxicities in childhood cancer patients - Tacyildiz, N.; Ozyoruk, D.; Yavuz, G.; Unal, E.; Dincaslan, H.; Dogu, F.; Kucuk, O. (Amer Soc Clinical Oncology, 2010)
[Abstract Not Available]